2022
DOI: 10.1186/s13643-022-01966-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of adherence to prescribed exercise programs for older adults with medical or surgical indications for exercise: a systematic review

Abstract: Background and objectives Prescribed exercise to treat medical conditions and to prepare for surgery is a promising intervention to prevent adverse health outcomes for older adults; however, adherence to exercise programs may be low. Our objective was to identify and grade the quality of predictors of adherence to prescribed exercise in older adults. Methods Prospective observational and experimental studies were identified using a peer-reviewed se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 82 publications
(57 reference statements)
2
18
0
Order By: Relevance
“…The research team conducted exercise teaching and supervision, controlling the intensity of the exercise for the older adults when implementing the plan; thus, through group exercise, social support was engendered, such as increasing social opportunities and establishing mutual network communities. The fact that the exercise intervention virtually established adherence was a result, which was consistent with many studies [52,[106][107][108][109].…”
Section: Discussionsupporting
confidence: 83%
“…The research team conducted exercise teaching and supervision, controlling the intensity of the exercise for the older adults when implementing the plan; thus, through group exercise, social support was engendered, such as increasing social opportunities and establishing mutual network communities. The fact that the exercise intervention virtually established adherence was a result, which was consistent with many studies [52,[106][107][108][109].…”
Section: Discussionsupporting
confidence: 83%
“…Surprisingly, self‐efficacy for exercise was negatively associated with exercise adherence, contradicting previous research 29,30,39–41 . This could be due to overestimation of task demands when requirements are unclear, while underestimation leads to underconfidence 42 .…”
Section: Discussionmentioning
confidence: 58%
“…31 In other exercise settings, similar results were reported for physical activity history, but no clear evidence was found regarding whether a previous exercise history predicts exercise adherence. 17,31 In contrast to existing literature, the results of our analysis revealed that BMI, health status and quality of life were not predictors of exercise adherence. Exercise self-efficacy was a positive predictor only in our univariate analysis.…”
Section: Association Between User Acceptance and Change In Exercise S...mentioning
confidence: 55%
“…31 Regarding demographic factors, age and sex did not affect exercise adherence in the included exercise interventions of the systematic review. 31 In other exercise settings, similar results were reported for physical activity history, but no clear evidence was found regarding whether a previous exercise history predicts exercise adherence. 17,31 In contrast to existing literature, the results of our analysis revealed that BMI, health status and quality of life were not predictors of exercise adherence.…”
Section: Association Between User Acceptance and Change In Exercise S...mentioning
confidence: 92%